The Development and Application of Novel IR and NMR-Based Model for the Evaluation of Carminative Effect of Artemisia judaica L. Essential Oil - Muhammed Alzweiri; Ibrahim M. Alrawashdeh; Sanaa K. Bardaweel (International Journal of Analytical Chemistry)
Artemisia judaica L. is a medicinal plant that is traditionally used to relieve abdominal pains through its carminative activity. In this study, spectroscopic analysis was employed to investigate the carminative activity associated with A. judaica. Using infrared spectroscopy, the carminative activity was evaluated based on the first derivative of IR-characteristic stretching signal of CO2. Our results indicate that A. judaica oil effectively reduced the response of CO2 signal equivalent to thymol standard. Additionally, 1H-NMR spectroscopy was utilized to assess surface activity of A. judaica crude oil through the reduction of interfacial tension in a D2O/CDCl3 system. Apparently, 10 mg of the oil was able to solubilize water in a chloroform layer up to 4.3% (w/w). In order to correlate the observed surface activity of the oil to its actual composition, GC-MS and GC-FID structural analysis were undertaken. The results revealed that the oil composition consists of oxygenated terpenes which might be responsible for the carminative effect. Furthermore, owing to its sensitivity, our model provides a fundamental basis for the pharmacological assessment of trace amounts of oils with high precision and accuracy.